Differences in Anthropometric Measures of Footballers, Cup Winners of Montenegro and Kosovo - Jovan Gardasevic; Dusko Bjelica; Ivan Vasiljevic; Fitim Arif; Sami Sermaxhaj (Journal of Anthropology of Sport and Physical Education, 2019)
The aim of this research was to determine the diff erences among the top football players of the Montenegrin club FC Sutjeska-Niksic and Kosovian club FC Besa Peje, the Cup winners in their countries, in the anthropometric measures and body composition. A sample of 41 examinees is divided into two sub-samples. The fi rst sub-sample of the examinees consisted of 23 players of FC Sutjeska-Niksic of the average age of 21.69±4.30, the champions of the Cup of Montenegro in the season 2016/17, while the other sub-sample consisted of 18 players of FC Besa Peje of the average age of 21.83±3.17, the champions of the Cup of Kosovo in the season 2016/17. Football players were tested immediately after the end of the competition season 2016/17. Anthropometric measures in the body composition were evaluated by a battery of 10 variables: body height, body weight, waist size, triceps skin set, biceps skin set, back skin set, abdominal skin set, body mass index, fat percentage and muscle mass. The standard central and dispersive parameters of all variables are calculated. The signifi cance of the diff erences between the players of the top two football clubs in the anthropometric measures and variables for assessing body composition was determined by a t-test for independent samples. It was found that the football players of the two mentioned clubs have statistically signifi cant diff erences by the one variable that estimate the muscle mass in a favor of FC Sutjeska.